Optimizing Geophysics Models Using Thread and Data Mapping - Serpa, Matheus S.; Cruz, Eduardo H. M.; Panetta, Jairo; Navaux, Philippe O. A. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2018: Anais do XIX Simpósio em Sistemas Computacionais de Alto Desempenho, 2018)
Many software mechanisms for geophysics exploration in Oil & Gas industries are based on wave propagation simulation. To perform such simulations, state-of-art HPC architectures are employed, generating results faster at each generation. It is therefore of paramount importance to optimize their operation on modern processors. In this paper, we study the impact of thread and data mapping strategies, revealing that, with smart mapping policies, one can indeed significantly speed up these simulations on modern architectures. We reduced the execution time by up to 33.5% and 58.6% on Intel’s multi-core Xeon and many-core accelerator Xeon Phi Knights Landing, respectively.